Production Cost Analysis Using the Full Costing Method at Yabo Kopi Keliling Palu City - Rio Bagas Maulana; Sugianto Sugianto; Abdul Kahar; Latifah Sukmawati Yuniar (Journal of Economics and Management Scienties, 2026)
This study aims to analyze the determination of production costs at Yabo Kopi Keliling using the full costing method, in order to evaluate comprehensive cost calculations and identify cost management practices in a mobile coffee business. This study employed a descriptive qualitative approach, with data collected through direct observation, in-depth interviews, and documentation related to raw material costs, direct labor costs, and manufacturing overhead costs. Data analysis was conducted systematically through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the full costing method enables business owners to obtain comprehensive and accurate production cost calculations, encompassing all fixed and variable cost components. This cost information is utilized to control operational expenses, assess production efficiency, and support strategic decision-making in business management. Overall, the findings confirm that the full costing method is effective as a tool for improving production cost efficiency and supporting the operational sustainability of mobile coffee businesses. Furthermore, the implementation of this method assists the owner in establishing more competitive and precise pricing strategies to optimize profit margins. The detailed cost breakdown also minimizes the risk of financial leakage caused by overlooked indirect expenses common in micro-enterprises.